2011
DOI: 10.3354/meps09068
|View full text |Cite
|
Sign up to set email alerts
|

White-capped albatrosses alter fine-scale foraging behavior patterns when associated with fishing vessels

Abstract: Incidental bycatch of seabirds in commercial fishing activities is known to cause declines in seabird populations. However, the full impacts on the ecology of seabirds, including effects on seabird distribution and behavior, through the association with fisheries are not fully understood. We developed a novel method to integrate fine-scale GPS tracking data from the foraging trips of 25 white-capped albatross Thalassarche steadi within sub-Antarctic New Zealand with fishing effort distribution data to (1) quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 23 publications
4
70
0
Order By: Relevance
“…The observed heterogeneity in survival may correspond to two types of individuals that reflect behavioral syndromes, such as those strongly attracted by fishing vessels and therefore susceptible to capture and mortality by longlines, and those less attracted by fishing vessels and less susceptible to capture. Indeed, recent studies showed that some individuals appear to be more attracted to fishing vessels than others on a handful of seabird species [32], including albatrosses [33], [34]. Harvesting, fishing or trapping can produce within-species differential vulnerability in target species [6], [12], [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed heterogeneity in survival may correspond to two types of individuals that reflect behavioral syndromes, such as those strongly attracted by fishing vessels and therefore susceptible to capture and mortality by longlines, and those less attracted by fishing vessels and less susceptible to capture. Indeed, recent studies showed that some individuals appear to be more attracted to fishing vessels than others on a handful of seabird species [32], including albatrosses [33], [34]. Harvesting, fishing or trapping can produce within-species differential vulnerability in target species [6], [12], [14].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the observation that within a population of a given seabird species some individuals appear to be more attracted to fishing vessels than others [32], including albatrosses [33], [34], we hypothesize that this held for our study population of albatrosses, and can account for the paradoxical population trend. The population is assumed to be heterogeneous, with two types of individuals that reflect behavioral syndromes (animal personalities): those strongly attracted by fishing vessels and therefore susceptible to capture and mortality by longlines; and those less attracted by fishing vessels and therefore less susceptible to capture.…”
Section: Introductionmentioning
confidence: 91%
“…The repeatability of an individual's foraging behaviour has been demonstrated in previous studies [35,54] whereas others report changes in foraging behaviour. For example, Torres et al [55] found that the white-capped albatross Thalassarche steadi had highly variable and adaptable foraging destinations in response to fisheries.…”
Section: Discussionmentioning
confidence: 98%
“…We recorded incubation foraging trips of adult albatross (n = 24) after securing the GPS tag to back feathers using Tesa ® tape. To focus on at-sea behaviors we removed all points within 5 km of the colony [16]. We completed all analysis in R [17] and implemented in C, with adapted code from Chirico [18] and Kahle and Wickham [19].…”
Section: Methodsmentioning
confidence: 99%